PENGARUH PERGANTIAN MANAJEMEN DAN FINANCIAL DISTRESS TERHADAP AUDITORSWITCHING SECARA VOLUNTARY - Erna, Wa; Atarwaman, Rita J. D.; Usmany, Alfrin Ernest Marthen (Kupna Akuntansi: Kumpulan Artikel Akuntansi, 2023)
This study aims to obtain empirical evidence of the effect of management change and financial distress on voluntary auditor switching. This research was conducted on mining companies listed on the Indonesia Stock Exchange for the 2013-2021 period. The number of samples was 7 companies with 9 years of observation and obtained 63 observations. The sampling method used purposive sampling. Auditor switching in this study uses a dummy variable proxy. The analysis technique was carried out using logistic regression analysis techniques using the SPSS version 25 application. The results of the study show that management turnover has no significant effect on auditor switching. Financial distress has no significant effect on auditor switching.